DIREITOS HUMANOS E O EXERCÍCIO DA CAPACIDADE POLÍTICA PASSIVA: A REFORMA À LEI DE IMPROBIDADE ADMINISTRATIVA E OS NOVOS PARÂMETROS DE LEGALIDADE À LEI DA FICHA LIMPA - Arthur Gabriel Marcon Vasques (2022)
Political rights in Brazil were built due to a lot of social movement, reason why history is full of advances and setbacks that marked its eras and, in the process of constitutionalism, forged dimensions of fundamental rights. In terms of legislative limitations on political rights, which are legitimate, the Complementary Law n. 135/2010 is one of the recent examples that brought serious consequences to the exercise of this category of rights, related to the indefinition and possible perpetuity of the sentence. The rationale for the research, therefore, is related to the perception that the constitutional intention of removing from public life those who do not have minimum conditions for the execution of a decent and moral public service cannot be seen as a way of punishing the citizen for an indefinite and perpetual time, in order to banish him from public service. From this perspective, the problem that guides the research seeks to identify — since the application of Complementary Law n. 135/2010 makes the period of ineligibility indeterminable — whether the new Administrative Improbity Law can be a resource for adapting the matter to constitutional principles and broad democratic participation in the exercise of citizenship. The research aims to analyze the effects of the application of Federal Law n. 14.230/2021, which brought correction mechanisms to the abuses perpetrated by Complementary Law n. 135/2010 related to the deadlines in which the public agent will be prevented from exercising the fullness of his political rights, when being sentenced of an act of administrative improbity. To carry out the research, the hypothetical-deductive method will be used, before of the finding of a gap in knowledge about the effects of the reform in the Administrative Improbity Law related to the delay in the course of the restriction of political rights. In conclusion, fundamental political rights could not be arranged and relativized as happened in the approval of Complementary Law n. 135/2010, because it restricted the broad exercise of citizenship; as well as, because of its generality and lack of temporal taxation, it created a serious legal consequence (ineligibility) without a specific period of duration, because it anticipated the beginning of its effects for the condemnatory decision by a collegiate judgment. In this context, the new Administrative Improbity Law provides means of curbing or alleviating the abuses of the improper application of penalties to the sentenced person for an act of administrative improbity, such as the stipulation of a statute of limitations in the process and the detraction in the execution of the sentence.